Momentum removal to obtain the position‐dependent diffusion constant in constrained molecular dynamics simulation. Issue 30 (18th August 2021) - Fujimoto, Kazushi; Nagai, Tetsuro; Yamaguchi, Tsuyoshi
Abstract: The position‐dependent diffusion coefficient along with free energy profile are important parameters needed to study mass transport in heterogeneous systems such as biological and polymer membranes, and molecular dynamics (MD) calculation is a popular tool to obtain them. Among many methodologies, the Marrink–Berendsen (MB) method is often employed to calculate the position‐dependent diffusion coefficient, in which the autocorrelation function of the force on a fixed molecule is related to the friction on the molecule. However, the diffusion coefficient is shown to be affected by the period of the removal of the center‐of‐mass velocity, τ v 0, which is necessary when performing MD calculations using the Ewald method for Coulombic interaction. We have clarified theoretically in this study how this operation affects the diffusion coefficient calculated by the MB method, and the theoretical predictions are proven by MD calculations. Therefore, we succeeded in providing guidance on how to select an appropriate τ v 0 value in estimating the position‐dependent diffusion coefficient by the MB method. This guideline is applicable also to the Woolf–Roux method. Abstract : The position‐dependent diffusion coefficient is beneficial for studying mass transport with molecular dynamics calculations. In the Marrink–Berendsen method, this coefficient can be obtained from the integral of force autocorrelation function of a fixed molecule at an absolute position. However, the integrated values evaluated so in a finite system diminishes due to momentum flows arising from momentum conservation, and the diffusion coefficient diverges unphysically. We rigorously demonstrate that frequent removals of total momentum eliminate this flaw.